Analysis Quality Control in Project Development Warehouse PT Santos Jaya Abadi Sidoarjo Using the Process Decision Program Chart Method - Yohanes Usman Nandyanto; Michella Beatrix; Masca Indra Triana (Universitas Sebelas Maret, 2023)
Abstract: The rapid development of the construction world today, competition in the construction world is also increasingly fierce so that assurance and control of quality are demanded higher. One form of realization in facing competition and meeting these demands is the preparation of quality control. The purpose of this study is to determine the implementation of quality control in warehouse construction projects and to determine the risk analysis of existing structural work so that quality control can be implemented better. This research begins with data collection through a questionnaire method distributed to construction project workers, with respondents being the project managers to workers. Furthermore, the collected questionnaire data was analyzed using BIM SPSS and the process decision program chart method. The results of the analysis show that the implementation of warehouse construction projects, especially in column and beam structure work, has a percentage of 76%, and in-floor plate work has a percentage of 72%. So that quality control is carried out effectively and level risk at a medium risk level.